MEDAN MAKNA AKTIVITAS TANGAN DALAM BAHASA DAYAK BAKATI’ SUBAH - Deviyanti, Resty; Madeten, Sisilya Saman; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractHand activity is the ability of the limbs from shoulder to fingertips to take action or reaction such as holding, throwing, opening, touching, wearing, hurting, destroying, covering, taking, carrying, pulling, inserting, putting, giving, arranging, mixing, cleaning, and emotional expression. A common problem in this research is the field of meaning of hand activity in the dayak language of bakati’ subah. Common problems are limited to three subproblems related to (1) the lexeme, (2) the component of meaning, and (3) the hyponimic chart. The purpose of this study is the description of all lexeme, component of meaning, and hiponimic chart. The method used in this research is descriptive method and qualitative research form. Data source in this research that is informant and its data is lexeme about hand activity in dayak language of bakati’ subah. The technique used in this research is the interview technique while the data collection tool is a recorder, camera, and notebook. Based on the result of data analysis found 19 hand activities is hand holding, throw, open, hurts, touch, wearing, destroy, cover, take, bring, interesting, insert, put, giving, arranged, mix, twisting, cleaning, and emotion expression. Keywords: meaning field, hand activity, Dayak language Bakati’ Subah.